New phosphated poly(methyl methacrylate) polymers for the prevention of denture-induced microbial infection: an in vitro study - Periathamby Antony Raj; Andrew R Dentino (Dove Medical Press, 2011)
Periathamby Antony Raj1, Andrew R Dentino1,21Division of Research and Development, Perident Therapeutics, Inc, Milwaukee, WI, USA; 2Division of Periodontics, Department of Surgical Sciences, Marquette University, Milwaukee, WI, USAPurpose: Poly(methyl methacrylate) (PMMA) has been widely used as a denture-base acrylic resin due to its excellent physical and mechanical properties. However, the material is highly prone to microbial fouling that often leads to Candida-associated denture stomatitis. Incorporation of phosphate groups into PMMA could facilitate adsorption of salivary antimicrobials and inhibit microbial adherence on the polymer surface. An in vitro study evaluated PMMA polymers containing varying amounts of phosphate group for their efficacy to inhibit Candida albicans adhesion, adsorb salivary histatin 5, and exhibit candidacidal activity.Methods: Six PMMA polymers containing 0%, 5%, 15%, 10%, 20%, and 25% of phosphate group were synthesized by bead (suspension) polymerization technique using mixtures of methyl methacrylate and methallyl phosphate as monomers. The efficacy of the polymers to inhibit the adherence of C. albicans was examined by using human saliva-coated polymer beads and radio-labeled C. albicans cells, as compared with that of PMMA. The potency of the phosphated PMMA polymers to adsorb histatin 5 was determined by measuring the radioactivity of the adsorbed labeled-peptide on the polymer surface. The candidacidal activity of the histatin 5-adsorbed polymers was assessed by using the fluorescence technique. The percent release of the fluorescent probe calcein from the C. albicans membrane caused by the disruption of the cell membrane was determined. The data were analyzed statistically by one-way ANOVA followed by Scheffé’s test (α = 0.05 and n = 6).Results: The presence of ≥15% phosphate content in PMMA significantly reduced the saliva-mediated adhesion of C. albicans. Phosphated PMMA polymers showed significantly enhanced adsorption of histatin 5 in a phosphate density-dependent manner. The candidacidal activity of the histatin 5-bound polymers increased significantly with the increase in the phosphate content of the polymer.Conclusion: Phosphated PMMA polymers have the potential to serve as novel denture-base resins, which may reduce C. albicans colonization and prevent denture stomatitis.Keywords: phosphated poly(methyl methacrylate) polymers, denture infection, Candida albicans adhesion, salivary antimicrobials, histatins